Current Issues in the Study of the Place of Cryptocurrency and Digital Money Technology in the Digital Economy (Texas Journal of Multidisciplinary Studies, 2023)
Nowadays, it is very important and focused on the methodological and legal application of cryptocurrency. The system of direct payments was a response to the global and financial crisis, the consequences of which shook the financial system of the countries of the world. This allows to determine a number of advantages and disadvantages of the new currency based on the data. Along with the technological advantage in this direction, there are still questions about the methodological and legal components of cryptocurrency. Bitcoin is mainly characterized by decentralization: a special program code regulates the work of network members, as well as the emission schedule, which is self-restricted. The introduction of cryptocurrency has a number of other positive effects: irreversible transactions, low transfer fees, complete isolation of the currency from inflation. At the same time, cryptocurrency has negative consequences. For example, the impossibility of tracking money transfers and the weakness of the system create conditions for illegal operations: capital embezzlement, terrorism, etc. Another negative feature of cryptocurrency is its dependence on supply and demand.